Type Synthesis and Classification of 1-translational and 2-rotation Parallel Mechanism - Feng Yongping; Luo Yufeng; Shi Zhixin; Xie Dongfu (Jixie chuandong)
Using topological structure synthesis method Based on the POC set,the type synthesis of 1-translational and 2-rotation parallel mechanism is carried out. The general steps and concrete operation methods of topological structure design of a 1-translational and 2-rotation parallel manipulator is given. Many kinds of mechanisms are obtained based on this approach,including some previously designed mechanisms and some new mechanisms,and these mechanisms are analyzed and classified.